Secondary Tax Liability / In Dubio Contra Reum - Drobnjak, Bojana (Zbornik radova Pravnog fakulteta u Novom Sadu, 2025)
Secondary tax liability in domestic law is structured as an instrument aimed at suppressing (un)lawful tax evasion by extending fiscal responsibility to persons who are not primary taxpayers. The application of this institute indicates a tendency toward functional convergence of tax law solutions with repressive models characteristic of criminal law. This is particularly evident in the introduction of a subjective element—culpability—as a condition for establishing secondary liability, which represents a key distinction from classical instruments of tax collection enforcement. Such a legislative construct necessarily raises the question of the legal nature of the norm itself: whether it constitutes an administrative law mechanism with a repressive effect, or a criminal law measure disguised in a tax law form. The hypothesis in this article is based on the identified conflict between secondary liability as a tax policy instrument for combating harmful behavior, on the one hand, and consistent application of the principle of legal certainty, on the other. The findings of the research indicate a need for more precise regulation of this institute in order to provide greater legal certainty for taxpayers. The legislative framework should clearly define the legal character and boundaries of secondary tax liability, and address the standards for evaluating culpability, the prioritization of claims, and the conditions under which recourse may be exercised. Reform of this anti-abuse measure requires an analytical approach by the legislator in order to align tax objectives with constitutional law standards.